Investigation of the Effects of Probation Practices on Restorative Justice System - Şekerci, Cansu; Aşıcıoğlu, Faruk (The Bulletin of Legal Medicine, 2021)
Objective: In this study, it was tried to determine disadvantages by means of investigating the effects of probationers’ life in the implementation of probation practices which is an element of restorative justice and it was aimed to find suggestions that will improve the practice. Methods: Using the phenomenological analysis method, Questions were asked during in-depth interviews to eight probationers in different process of the probation and three experts were interviewed. To evaluate how they make sense of restorative justice and how they were affected by the probation process to participants. Results: Due to experiences share the by participants, it has been determined that the probation processes can turn into a stigmatization system that prevents social compliance of the probationers and the measures are not determined according to probationers’ risks and needs. Also, it violets the presumption of innocence in the perception of third parties at the trial stage and the function of deterrence from crime is not satisfactory. Conclusion: It can be ensured that probation services serve more to restorative justice by methods such as ensuring social cohesion by taking into account the risks and needs of probationers, the probationer at the trial stage benefiting from the presumption of innocence, and individualizing the process. These suggestions will be possible with the improvements in this direction without the need for changes in the existing legislation.